1990
DOI: 10.5962/bhl.title.53728
|View full text |Cite
|
Sign up to set email alerts
|

Poisonous plants of Canada

Abstract: Animals No information. Abrus precatorius, 31 Acer ruhrum, 10 Aconitum napellus, 41 Aesculus hippocastanum, 30 Agrostemma githago, 19 Ailanthus altissima, 44 Allamanda cathartica, 12-13 Allium spp., 34-35 A/oe spp., 35 Amaranthus spp., 10 Amaryllis spp., 10-11 Amsinkia intermedia, 17 Anagallis arvensis, 41 Anthurium spp., 14 Apocynum spp., 13 Arisaema triphyllum, 14 Asarum canadense, 16 Asclepias spp., 16 Asimina triloba, 12 Astragalus spp., 31 Bap^isia spp., 32 Barbarea vulgaris, 24 Bassia hyssopifolia, 20 Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Studies of Dieffenbachia demonstrated that proteolytic enzymes, as well as other compounds, are responsible for the severe irritation caused by this plant and this has resulted in it being included in many lists of poisonous plants (Perkins and Payne, 1978;Lampe and McCann, 1985;Mulligan and Munro, 1990). The antimicrobial assays of the leaves and stems of Dieffenbachia picta have been carried out by Hewitt and Measurements and data analysis All microscopic measurements were taken with the aid of an ocular micrometer inserted into the eyepiece of a microscope.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Dieffenbachia demonstrated that proteolytic enzymes, as well as other compounds, are responsible for the severe irritation caused by this plant and this has resulted in it being included in many lists of poisonous plants (Perkins and Payne, 1978;Lampe and McCann, 1985;Mulligan and Munro, 1990). The antimicrobial assays of the leaves and stems of Dieffenbachia picta have been carried out by Hewitt and Measurements and data analysis All microscopic measurements were taken with the aid of an ocular micrometer inserted into the eyepiece of a microscope.…”
Section: Introductionmentioning
confidence: 99%
“…~o t a b l e systematic contributions about plants that poison livestock in Canada are Mulligan and Munro (1990) and Munro (1993).…”
Section: Agricultural Utilization Of Natural Standsmentioning
confidence: 99%
“…are usually not mentioned among toxic plants in North America (e.g., Evers and Link 1972;Stephens 1980;Lampe and McCann 1985;Mulligan and Munro 1990), dodders have been suspected to be toxic to humans (Perkins and Payne 1978) and livestock (Kingsbury 1964). Movsesyan and Azaryan (1974) reported that C. campestris can be poisonous to animals if it exceeds 5% of the total roughage.…”
Section: Cuscuta Umbrosamentioning
confidence: 99%